The Karaite Jewish community in Israel (20th and 21st centuries) - Firrouz, Moshe (Karaite Archives, 2013)
The academic world has at its disposal a vast quantity of resources concerning the history and culture of the Karaite Jewish community. These resources include Biblical manuscripts, works on Biblical exegesis and Halakhah (Jewish law), grammatical texts, letters on community affairs, wedding contracts and other important texts that shed much light upon Karaite religious observance, history, and culture. The aim of this paper is to present to the reader in a concise manner the facts regarding the development of the Karaite Jewish community in Israel in the 20th and 21st century. In addition, it endeavors to describe the relationship between the Karaite Jewish community and other communities, in particular the Rabbinate Jewish community in Israel and the USA.